Menilik Pertanggungjawaban Penyelenggaraan Pemerintahan Gampong Menurut Qanun Gampong No. 1 Tahun 2019 - Siregar, Friska Anggi (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2023)
Gampong Aceh Qanun No. 1 of 2019 concerns the Gampong government regulating gampong governance administration. The Keuchik as the gampong government, must submit a government responsibility report to Tuha Peut Gampong and the Mayor through the camat. The report consists of three parts: the year-end report on the administration of gampong governance, the final report on the administration of gampong governance at the end of the period, and the information report on the administration of gampong governance at the end of the fiscal year. Keuchik reporting activities are funded by the Gampong Revenue and Expenditure Budget (APBG), and the procedures for submitting Keuchik accountability reports are regulated in a Mayor Regulation. With this rule, it is hoped that the Gampong Aceh administration will become more accountable and transparent.